Impact of blood pressure and medication adherence on clinical outcomes in patients with hypertension - Kim, Hyun-Jin; Kim, Byung Sik; Kim, Hasung; Lee, Jungkuk; Shin, Jeong-Hun; Sung, Ki-Chul (Frontiers in Medicine, 2025)
BackgroundHypertension is a key risk factor for cardiovascular disease. Thus, effective blood pressure (BP) management and adherence to antihypertensive medications are crucial for reducing these risks in patients with hypertension. We evaluated the effect of BP and medication adherence on the clinical outcomes of patients with hypertension.MethodsThis is retrospective cohort study utilized data from the Korean National Health Insurance Database. We analyzed data from 238,950 patients with hypertension aged ≥20 who underwent at least two health checkups between 2009 and 2012. Patients were categorized according to their systolic BP (SBP) and medication adherence. The primary outcome was a composite of all-cause death, myocardial infarction, ischemic stroke, hemorrhagic stroke, and hospitalization for heart failure. Cox proportional hazard models were used to estimate hazard ratios (HR) for composite outcomes.ResultsHigher SBP groups were associated with increased risk of composite outcomes compared to the 120–129 mmHg group (<120 mmHg, HR 1.065; 130–139 mmHg, HR 1.056; 140–149 mmHg, HR 1.068; and ≥150 mmHg, HR 1.238). In addition, across all SBP categories, poor adherence significantly elevated the risk of composite outcomes, even after adjusting for confounding factors. Among all categories, patients with high SBP (≥150 mmHg) and poor adherence had the highest risk.ConclusionHigher SBP and poor medication adherence were independently associated with worse clinical outcomes in patients with hypertension. Strategies to enhance medication adherence and achieve optimal BP control are essential to reduce cardiovascular risk.